2014
DOI: 10.1007/s12671-014-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mindfulness and Mindfulness with Self-Compassion-Centered Interventions to Assist Weight Loss: Theoretical Considerations and Preliminary Results of a Randomized Pilot Study

Abstract: This research explored whether developing mindfulness and self-compassion through meditation supports weight loss. The research addressed if (a) mindfulness meditation and (b) mindfulness with self-compassion Meditation (through loving kindness meditation and psychoeducational material to develop self-compassion) aid weight loss and maintenance. Sixty-three soldiers followed independent diet plans and were randomly assigned to a control group, or, one of the two meditation interventions for 5 weeks. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 52 publications
5
119
1
3
Order By: Relevance
“…The most frequent strategies are based on the regulatory skills and correspond to new approaches within the cognitivebehavioural psychological therapies. So, mindfulness therapy, acceptance and commitment therapy, self-compassion therapy (loving-kindness therapy), emotionally focused therapy and dialectical behaviour therapy lead to less psychological distress (130)(131)(132)(133)(134) , fewer binge eating episodes (130,131,135) , less emotional eating (136) , fewer food cravings (136)(137)(138) , healthier eating patterns (131,139) , weight loss (131,132,134,138) , fewer personal barriers to physical activity (140) , and improved self-efficacy to weight loss (141) . Despite a few non-significant findings (142) , these strategies are a promising approach for obesity treatment and prevention.…”
Section: Interventions In Adultsmentioning
confidence: 99%
“…The most frequent strategies are based on the regulatory skills and correspond to new approaches within the cognitivebehavioural psychological therapies. So, mindfulness therapy, acceptance and commitment therapy, self-compassion therapy (loving-kindness therapy), emotionally focused therapy and dialectical behaviour therapy lead to less psychological distress (130)(131)(132)(133)(134) , fewer binge eating episodes (130,131,135) , less emotional eating (136) , fewer food cravings (136)(137)(138) , healthier eating patterns (131,139) , weight loss (131,132,134,138) , fewer personal barriers to physical activity (140) , and improved self-efficacy to weight loss (141) . Despite a few non-significant findings (142) , these strategies are a promising approach for obesity treatment and prevention.…”
Section: Interventions In Adultsmentioning
confidence: 99%
“…Furthermore, people who eat more mindfully, or participate in mindfulness meditation programmes have been found to improve the way they eat and successfully eat less [9][10][11][12][13][14]. However, Mantzios and Wilson [13] suggested that the combination of mindfulness and self-compassion might be more beneficial than mindfulness alone, and this was subsequently evidenced in other studies [15].…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study with restrictive eaters, Adams and Leary [20] used a short self-compassionate intervention with people who had broken their diet and found that this prolonged increase in food intake did not occur. Furthermore, recent research indicates that self-compassion plays a significant role across many aspects of weight regulation, in maintaining weight [18], in weight loss [15], and with different mindful practices (i.e., diaries instead of meditation) [13]. Other research suggests that selfcompassion may also provide positive outcomes in disordered eating.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a recent review exploring the relationship between self-compassion and obesity (see Mantzios & Egan, 2017), it was suggested that reporting findings from the subscales of those traits might offer further insights. Another review suggested investigating mindful eating more specifically, to identify more relevant and useful associations in obesity research (Mantzios & Wilson, 2015a). The overall aim of this research is to clarify the relationship of mindfulness, mindful eating and self-compassion to BMI through the use of a recent scale that assesses the motivations behind eating palatable foods.…”
mentioning
confidence: 99%